A rare case of upper labial frenulum causing functional and aesthetic impairment: surgical management with frenuloplasty - Choudhary, Ruchi; Arora, Bhavinder Kumar (International Surgery Journal, 2025)
The superior labial frenulum, connecting the upper lip to the maxillary gingiva, can exhibit variations in attachment and morphology leading to functional and aesthetic concerns. This case report discusses a five-year-old male presenting with an increased gap between upper central incisors, speech difficulties, and restricted lip movement due to a thick upper labial frenulum. Surgical intervention through a frenuloplasty was performed after conservative measures failed. A "Z" shaped incision allowed for the detachment and repositioning of the frenulum to enhance lip alignment. Post-surgery, the patient demonstrated improvements in speech and lip mobility, with the potential for orthodontic treatment to address the diastema. This case underscores the importance of early identification and surgical correction of frenulum anomalies, resulting in significant functional and cosmetic benefits. Monitoring over two weeks confirmed the surgery's success.